2014
DOI: 10.1111/apha.12395
|View full text |Cite
|
Sign up to set email alerts
|

Exercise increases the binding of MEF2A to the Cpt1b promoter in mouse skeletal muscle

Abstract: Our results indicated that exercise-induced CPT1b expression was at least in part mediated by HDAC5/MEF2A interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 27 publications
2
27
0
Order By: Relevance
“…Exercise benefits at the molecular level are linked, in part, to transcriptional activation myocyte-specific enhancer factor (MEF) 2A in coordination with PPAR-γ, PPARGC1a, and acetylation of GLUT4 in the skeletal muscle [53]. It has been recently shown that exercise increases the binding of MEF2A to the Cpt1b promoter in the mouse skeletal muscle and this requires repression of MEF2A-binding partners such as HDAC5 and HDAC3 [54]. Interestingly, a short-term intensive practice of mindfulness meditation has been demonstrated to rapidly decrease histone deacetylases (more strikingly HDAC3) and inflammatory gene expression [55] implying that appropriate lifestyle modifications may offer metabolic benefits operating through epigenetic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise benefits at the molecular level are linked, in part, to transcriptional activation myocyte-specific enhancer factor (MEF) 2A in coordination with PPAR-γ, PPARGC1a, and acetylation of GLUT4 in the skeletal muscle [53]. It has been recently shown that exercise increases the binding of MEF2A to the Cpt1b promoter in the mouse skeletal muscle and this requires repression of MEF2A-binding partners such as HDAC5 and HDAC3 [54]. Interestingly, a short-term intensive practice of mindfulness meditation has been demonstrated to rapidly decrease histone deacetylases (more strikingly HDAC3) and inflammatory gene expression [55] implying that appropriate lifestyle modifications may offer metabolic benefits operating through epigenetic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of AMPK leads to phosphorylation and nuclear exclusion of class IIa HDACs, which relieves repression of myocyte enhancer factor‐2 (MEF2), a transcription factor that regulating the transcription of PGC‐1α and GLUT4 . Our previous study showed that CPT1b expression was also regulated by HDAC5/MEF2A interaction . In the present study, we found that overexpression or knockdown of HSPB1 altered the phosphorylation of HDAC5 at Ser259/498 and HDAC4 at Ser246.…”
Section: Discussionmentioning
confidence: 48%
“…), and these changes were shown to be regulated in part by myocyte‐specific enhancer factor (Yuan et al. ). After 5 weeks of hypobaric hypoxia (simulated 4000 m), muscle CPT‐1 activity was shown to be markedly decreased in rat quadriceps muscles, whereas these activity levels reached those of normoxic sedentary controls after exercise training under hypoxia, which indicated that exercise training restored muscle CPT activity in the hypoxic environment (Galbès et al.…”
Section: Discussionmentioning
confidence: 99%
“…Aerobic exercise training for 6 weeks markedly increased CPT-1 mRNA and protein levels in mice skeletal muscle (Niu et al 2010), and these changes were shown to be regulated in part by myocyte-specific enhancer factor (Yuan et al 2014). After 5 weeks of hypobaric hypoxia (simulated 4000 m), muscle CPT-1 activity was shown to be markedly decreased in rat quadriceps muscles, whereas *, significantly different from the Cnt group at P < 0.05 using a one-way ANOVA followed by Tukey's post hoc test and 95% confidential interval did not contain the parameter value specified in the null hypothesis.…”
Section: Chronic Response Of Exercise Training With Intermittent Hypomentioning
confidence: 93%